2021
DOI: 10.7861/clinmed.2020-0204
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sequelae following previous coronavirus epidemics

Abstract: Before the current pandemic, there had been two global epidemics from major coronavirus outbreaks since the turn of the century: severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV). Both epidemics left survivors with fatigue, persistent shortness of breath, reduced quality of life and a significant burden of mental health problems. It is likely that some of the chronic problems encountered by survivors of SARS and MERS may be relevant for medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
81
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 28 publications
10
81
0
7
Order By: Relevance
“…Interestingly, similar observations of long-term sequelae has been reported following the SARS-CoV-1 outbreak of 2003 (22), and Middle East Respiratory Syndrome (MERS) outbreak of 2012 as well (23). The survivors from the previous two CoV epidemics were found to experience persistent shortness of breath, fatigue, mental health problems and reduced quality of life that constituted a kind of post-acute viral syndrome (23). A oneyear follow-up study of SARS survivors reported a significant reduction in mental health (24).…”
Section: Definition Of Post-acute Covid-19supporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, similar observations of long-term sequelae has been reported following the SARS-CoV-1 outbreak of 2003 (22), and Middle East Respiratory Syndrome (MERS) outbreak of 2012 as well (23). The survivors from the previous two CoV epidemics were found to experience persistent shortness of breath, fatigue, mental health problems and reduced quality of life that constituted a kind of post-acute viral syndrome (23). A oneyear follow-up study of SARS survivors reported a significant reduction in mental health (24).…”
Section: Definition Of Post-acute Covid-19supporting
confidence: 74%
“…In addition to posing as risk factors for the disease itself, factors such as age, frailty and presence of comorbidities, they also modulate the long-term impact of the disease. Interestingly, similar observations of long-term sequelae has been reported following the SARS-CoV-1 outbreak of 2003 (22), and Middle East Respiratory Syndrome (MERS) outbreak of 2012 as well (23). The survivors from the previous two CoV epidemics were found to experience persistent shortness of breath, fatigue, mental health problems and reduced quality of life that constituted a kind of post-acute viral syndrome (23).…”
Section: Definition Of Post-acute Covid-19supporting
confidence: 60%
“…This is important as there is considerable concern that COVID-19 disease triggers post-viral fatigue syndromes [26][27][28][29]. During follow-up in survivors of other coronaviruses, such as severe acute respiratory syndrome (SARS), 64% reported fatigue at 3 months, 54% at 6 months and 60% at 12 months [30,31]. Following Middle East respiratory syndrome (MERS), 48% had clinically relevant fatigue after 12 months [32].…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 Related coronavirus diseases, Middle East respiratory syndrome (MERS) and SARS, have also been shown to induce long-term metabolic changes in recovered patients pertaining to hypertriglyceridemia, disorders of glucose metabolism, and liver function, further underlying the considerable need to support recovery and repair of the body during the post-COVID period. 15 , 16 The similarities between the SARS-CoV-1 and SARS-CoV-2 outbreaks also extend to the neurological consequences, with 54% of patients experiencing fatigue and 60% experiencing sleep disturbances 6 months post infection. 17 In some patients recovering from severe infection, residual postmedication treatment side effects have been reported: (i) hydroxychloroquine and cardiotoxicity; and (ii) long-term use of painkillers and renal and gastrointestinal dysfunction.…”
Section: Introductionmentioning
confidence: 99%